Adjusting yearling weight ratios for prior selection - Vanmiddlesworth, J.; Schalles, R.R.; Milliken, George A. (Kansas State University. Agricultural Experiment Station, 2011)
We developed a procedure to compare yearling weight ratios of a calf crop when the calves have been on different management or feeding regimes This procedure will also produce more meaningful sire and dam summaries.
Keywords: Beef; Yearling weight; Weaning weight; Calf crop